Analysis of Correlation between Serum Inflammatory Factors and Cognitive Function, Language, and Memory in Alzheimer's Disease and Its Clinical Significance. (14th April 2022) - Lu, Yan; Li, Jie; Hu, Tingjun
Abstract : Objective. A case-control study was conducted to explore the correlation between serum inflammatory factor monitoring and cognitive function, language, and memory ability of Alzheimer's disease (AD) and its clinical significance. Methods . Thirty-six patients with AD treated from April 2019 to August 2021 in our hospital were enrolled as the study subjects (AD group), and 30 healthy volunteers from the physical examination center and the AD group with the same sex, age, education, and no complaints of memory loss were enrolled as the control group. Montreal Cognitive Assessment (MoCA) and AD Rating Scale-Cognitive (ADAS-cog) were employed to assess the cognitive function of AD and the control group. The Chinese Standard aphasia Test of China Rehabilitation Research Center (CRRCAE) was employed to assess the language function of AD and NC population. The World Health Organization-University of California, Los Angeles Auditory Word Learning Test (WHO-UCLAAV-LT) scale was employed to evaluate the memory function of AD group and control group. The levels of inflammatory factors in serum of the AD group and control group were detected by enzyme-linked immunosorbent assay (ELISA). The serum inflammatory factors levels were compared between the AD group and the control group, and the correlation between the level of serum inflammatory factors and cognitive function, language, and memory ability in the AD group was analyzed. Results . In terms of the demographic data of the two groups, there exhibited no significant difference in gender, age, education level, and other general data (P > 0.05 ). In terms of cognitive function, MoCA scores were remarkably lower compared to the AD group. In the comparison of memory ability, the scores of long-term delayed recognition, delayed memory, and instantaneous memory in the AD group were remarkably lower (P < 0.05 ). In the comparison of language ability, the scores of listening comprehension, reading, and naming in the AD group exhibited remarkably lower (P < 0.05 ). With regard to the levels of serum inflammatory factors, the levels of serum interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF- α ), and CCL-12 in AD group were remarkably higher, while the level of TNF- β in the AD group was lower compared to the control group. Furthermore, there exhibited no significant correlation between the levels of serum IL-4, IL-6, IL-10, TNF- α, CCL-2, and the total scores, MoCA, and ADAS-cog, but there exhibited a positive relationship between the level of serum TNF- β and the score of MoCA scale. The correlations between IL-4, IL-6, IL-10, TNF- α, TNF- β, CCL-2, and the scores of long-term delayed recognition, delayed memory, and instantaneous memory were analyzed in the AD group. The serum levels of IL-4, IL-6, IL-10, TNF- α, CCL-2, and TNF- β were not remarkably correlated with the scores of long-term delayed recognition, delayed memory, and instantaneous memory. The correlations between IL-4, IL-6, IL-10, TNF- α, TNF- β, CCL-2, and the scores of listening comprehension, reading, and naming were analyzed in the AD group, but with no significant correlation between the serum levels of IL-4, IL-6, IL-10, CCL-2, TNF- α, and TNF- β and the scores of listening comprehension, reading, and naming. Conclusion . Compared with the control group, the levels of serum IL-4, IL-6, IL-10, TNF- α, and CCL-2 in patients with AD exhibited remarkably higher, while the level of serum TNF- β exhibited remarkably lower. The level of serum TNF- β was remarkably correlated with cognitive function in patients with AD, which may reflect the severity of cognitive impairment in patients with AD.